Targeted point mutations of the m6A modification in miR675 using RNA-guided base editing induce cell apoptosis. Issue 5 (5th May 2020) - Hao, Jindong; Li, Chengshun; Lin, Chao; Hao, Yang; Yu, Xianfeng; Xia, Yidan; Gao, Fei; Jiang, Ziping; Wang, Dongxu
Abstract: Methylation of the adenine base at the nitrogen 6 position (m 6 A) is the most common post-transcriptional epigenetic modification of RNA, and it plays a very important role in regulating gene expression. To investigate the role of m 6 A methylation in the expression of non-coding RNA and miRNA, we used a system of adenine base editors (ABEs). Here, we mutated regions up- and downstream of miRNA 675 m 6 A modification sites in the H19 locus using HEK293T, L02, MHCC97L, MHCC97H, A549, and SGC-7901 cells. Our results showed that a T–A base transversion had occurred in all cell lines. Moreover, mutation of the regions upstream of the miRNA 675 m 6 A modification site led to reduced expression of H19 and the induction of cell apoptosis in HEK293T cells. To further confirm our results, L02 and MHCC97L cells were detected using ABEs system. The results indicated increased cell apoptosis and reduced expression of miR675 as well as H19 . To confirm the relationship between H19 and miR675 expression, overexpression and knockdown studies were performed. The results showed that reduced HI9 expression induced cell apoptosis through miR675. Taken together, these results indicate that m 6 A modification can regulate the expression of H19 and miR675 which induce cell apoptosis.